Optimalisasi Media Sosial Instagram Sebagai Media Promosi Produk UMKM Jatinegara Kaum - Dini Safitri; Nada Arina Romli (Jurnal Abdimas Perbanas, 2023)
Jatinegara Kaum Urban Village has made several programs for UMKM in their area. However, there are still a few UMKM actors who want to take advantage of the program, such as being active in the e-order program and optimizing Instagram social media as a promotional medium. For this reason, we are trying to help UMKM optimize Instagram social media for nine UMKM in Jatinegara Kaum. For UMKM that doesn’t have Instagram yet, we create an Instagram account, then work together to make uploads consisting of posters and videos which are then uploaded to Instagram UMKM. In addition, we also help to make the UMKM logo along with the tagline, so that UMKM are increasingly known by the wider community. As a result of this activity, UMKM feel helped in running their business. Their Instagram social media has also become optimal with weekly uploads accompanied by engagement with followers and non-followers. UMKM also gets knowledge about copywriting and visual product photos.